Highly Compact Design of Trimmed Patch with Modified Partial Ground Structure for Extreme-Wideband Systems - Alsaif, H. (Engineering, Technology & Applied Science Research, 2017)
In this paper, a novel highly compact microstrip monopole antenna with adjusted ground plane for ultra-wideband (UWB) applications is proposed. The patch antenna is composed of a trimmed radiator and rectangular ground plane with four slots providing relatively extreme wide operating frequency from 2.8 till 16.2 GHz based on -10 dB criteria. The high matching impedance in the design results in ultra-wide bandwidth that covers the entire BW allocated by FCC for UWB applications. At the same time, the presented antenna is distinguished by significantly miniaturized structure with total size of 13 mm x 10 mm printed on a substrate material of Rogers Duriod RT 5880 LZ with relative permittivity of εr=1.9 and loss tangent δ of 0.0009. The suggested antenna is appropriate for miniature wireless gadgets. The patch has been investigated, and optimized in terms of operating frequency, impedance matching, radiation characteristics, structure size, and fabrication cost.